Empowering nurse leaders: leveraging financial management practices to foster sustainable healthcare – a mixed-methods study - Hossam Ali Ismail; Mohamed Hashem Kotp; Hassan Ahmed Awad Basyouny; Aliaa Ezz Eldin Abd Elmoaty; Abdelaziz Hendy; Rasha Kadri Ibrahim; Sally Mohammed Farghaly Abdelaliem; Ahmed Hendy; Mohamed Ahmed Aly (BMC Nursing)
Abstract Introduction Nurse leaders play a crucial role in balancing financial sustainability and high-quality patient care. Their financial management skills impact patient safety, care quality, and satisfaction. However, many nurse leaders lack formal training in financial management, making it challenging to navigate budget constraints while maintaining care standards. Aim To assess nurse leaders’ perceptions of their financial management practices and explore their relationship to patient care quality and outcomes. Methods A convergent parallel mixed-methods approach was conducted with 87 nurse leaders in private hospitals across Egypt. Quantitative data (n = 87) were collected using the validated Nurse Leaders’ Financial Management Practices Assessment (NLFMP) tool, a 15-item instrument measuring budgeting, resource allocation, cost-effectiveness, decision-making, and its impact on patient care. The data were analyzed using SPSS. Concurrently, qualitative data from open-ended responses underwent thematic analysis. The results were then integrated to compare statistical trends with key themes, providing deeper insights into the financial decision-making challenges faced by nurse leaders. Results Findings indicated moderate financial management proficiency among 70% of participants, with high scores in decision-making influence (mean = 4.10 ± 0.48) and cost-effectiveness (mean = 4.05 ± 0.45). Budgeting practices (mean = 3.90 ± 0.50) and resource allocation (mean = 3.85 ± 0.55) were rated slightly lower, highlighting areas for improvement. The majority (87.3%) of nurse leaders perceived a strong relationship between financial management and patient care outcomes. Regression analysis showed that age (p = 0.010), educational attainment (p = 0.044), and employment status (p = 0.009) were significant predictors of financial management proficiency. Thematic analysis highlighted key challenges, including budget constraints, staffing shortages, and balancing cost-efficiency with care quality. Conclusion Nurse leaders perceive a strong link between financial management and patient care outcomes, emphasizing the need for targeted financial training and greater involvement in decision-making. Enhancing financial literacy among nurse leaders could foster better alignment between cost-efficiency and quality care, ensuring sustainable healthcare delivery. Clinical trial number Not applicable.